INVITED REVIEW: Detection and management of pregnancy loss in the cow herd - Speckhart, S. L.; Reese, S. T.; Franco, G. A.; Ault, T. B.; Oliveira Filho, R. V.; Oliveira, A. P.; Green, J. A.; Vasconcelos, J. L.M. [UNESP]; Pohler, K. G. (American Registry of Professional Animal Scientists, 2018)
Various methods and tools have been developed to detect and manage pregnancy loss in cattle to maximize reproductive efficiency by increasing pregnancy rates and decreasing pregnancy loss. Embryonic mortality constitutes the majority of pregnancy loss in cattle and can be divided into 2 periods: early embryonic mortality (<28 d of gestation) and late embryonic mortality/early fetal mortality (≥28 d of gestation). Much research has revolved around elucidating causes of early embryonic mortality; although little is known about the mechanisms contributing to late embryonic mortality/early fetal mortality, its effects can have significant economic consequences. Current pregnancy diagnostic tools in cattle vary in accuracy until about d 28 of gestation. Refinement of current pregnancy diagnostic tests, with the ability to be accurate at approximately the third week of gestation, or the development of new methods that are able to assess embryonic viability would both decrease the financial ramifications linked to embryonic mortality and increase the reproductive efficiency of the herd. The following review will highlight some techniques that have been reported to detect and predict pregnancy loss and some of the potential management strategies that might mitigate these losses.
Keywords: cattle; pregnancy detection; pregnancy diagnosis; pregnancy loss; pregnancy rate; reproduction